Diagnostic characteristics of fruits of some species of the Apiaceae family used in pharmacy: a comparative analysis - Dobrovolska, Yulia; Karpuk, Uliana; Makhynia, Larysa; Dvirna, Tetiana; Minarchenko, Valentina; Cholak, Irina; Kovalska , Nadiya; Pidchenko , Vitaliy (The Ukrainian Scientific Medical Youth Journal, 2025)
the wide use of plants of the Apiaceae family is accompanied by difficulties in identification, since their fruits have similar morphological characteristics. During the analysis, it became clear that there is a lack of detailed descriptions and accessible information about this family. The fruits characteristic of the Apiaceae family are often similar to each other within different species, which can complicate the identification of medicinal plant materials. Macroscopic characteristics remain an important element in establishing the authenticity of medicinal plant raw materials. That is why a detailed morphological description of the fruits of the Apiaceae family is necessary for their correct use in pharmacy and medicine. Within the framework of the study, a comprehensive analysis of the morphological characteristics of the fruits of representatives of the Apiaceae family was carried out, which is of great importance for their identification and standardization in pharmaceutical practice. A comprehensive analysis of scientific literature, the educational and professional program in specialty 226 “Pharmacy, Industrial Pharmacy,” integrated licensing exam programs (EDKI-1, KROK-2), and the methodological literature of Warsaw Medical University (WMU) to structure the data about the macroscopic features description of fruits of the Apiaceae family (Umbelliferae) representatives. A theoretical justification for the need for a unified approach to describing the fruits of this family has been provided. It has been established that the standardization of medicinal plant raw materials is a crucial stage in the production of medicinal products, as it involves the accurate identification and quality control of the raw materials. A review of the literature revealed discrepancies in the macroscopic description of the fruits of representatives of the family, which complicates the process of their reliable identification. Based on the analysis, the main morphological features of the fruits were determined. It can be used as criteria for classification and identification. It was found based on the studied sources and systematized materials, that the fruits of this family are characterized by the set of features. These features can be used as diagnostic markers for determining species affiliation. The generalization of the results made it possible to form a table of morphological features suitable for distinguishing between closely related species with similar fruits. This contributes to the reliability of the identification of medicinal plant raw materials and ensures the effectiveness of quality control of medicinal products. The practical value of the study lies in the prospect of applying the results obtained in the pharmaceutical field to the formation of pharmacopoeia standards, as well as in the field of pharmaceutical botany — for the classification and systematization of species of the Apiaceae family.